Stressors in adolescence: An analytical cross-sectional study - Ashok, Vidhu; Rajan, Aswathy; Maben, Roshan (Indian Journal of Child Health, 2017)
Objective: To understand the importance of stress in adolescence well-being, to categorize the stressors in them, and to understand the validity of their solutions. Materials and Methods: A prospective study was conducted in 804 students in the age group of 15-17 years from four schools in the city. Study was conducted with the help of “adolescent stress questionnaire” which consisted of 31 questions. An analysis of these answers was done to understand the stressors and other factors. Results: Out of 804 participants,43% (n=342) were females and 57% (n=462) were males. 52% (n=421) were 15-year-old, 32% (n=251) 16 years, and 16% (n=132) were 17-year-old. Academic stress is seen in 74%. No significant differences with gender are seen with the stress. Severe stress isless in children who are 17-year-old than those who are 15-year-old. Mild stress increases with age. Among the study participants, 50.9% (409) children mentioned that they did not get enough time to spend with their friends. Majority of the children were stressed due to studies (p=0.03) more than peer and parent relationship. At the time of break down, they preferred to watch television, listen to music and to use social media (WhatsApp or Facebook) rather than to speak out the matters that stressed them. 33.3% (268) of the adolescents felt that they need help in coping up with their stress. They enjoy what they are doing; though, grades in the school affect them and they feel more time to be spent for studies. Conclusion: Their main stressor was studied; though, a few of them stated that peer/parent/teacher relationships also affect them. Most of the adolescents are able to cope up with stressors in their own way but some of them feel that they need help.